2017
DOI: 10.1515/aoas-2016-0045
|View full text |Cite
|
Sign up to set email alerts
|

Association of Single Nucleotide Polymorphisms in the FABP4 Gene with Carcass Characteristics and Meat Quality in Holstein Bulls

Abstract: the aim of this study was to characterize the bovine fatty acid binding protein (FABP4) gene 3691g>A and 2834c>g polymorphisms and to evaluate interaction effects on the live weight, carcass characteristics and meat quality of holstein bulls in the south marmara region of turkey. A total of 400 holstein bulls grown on a private farm and slaughtered at 14-21 months of age, were randomly selected for use in this study. initially, genotyping was performed by pcr-rflp method and statistical analysis was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…For example they might affect the splicing of mRNA or be linked to variation elsewhere in a regulatory region (e.g., a miRNA binding site or enhancer binding site), or the 5 -UTR or 3 -UTR regions (UTR is untranslated region), that subsequently affects expression of the amino acid sequence (Wessagowit et al, 2005;MartõÂnez-Pizarro et al, 2018). Previous reports have demonstrated associations between genetic variation in FABP4 and carcass traits, meat quality traits, and fatty acid composition in adipocytes (Ardicli et al, 2017;Yan et al, 2018). Limited information is available regarding the effect of FABP4 on milk production traits in livestock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example they might affect the splicing of mRNA or be linked to variation elsewhere in a regulatory region (e.g., a miRNA binding site or enhancer binding site), or the 5 -UTR or 3 -UTR regions (UTR is untranslated region), that subsequently affects expression of the amino acid sequence (Wessagowit et al, 2005;MartõÂnez-Pizarro et al, 2018). Previous reports have demonstrated associations between genetic variation in FABP4 and carcass traits, meat quality traits, and fatty acid composition in adipocytes (Ardicli et al, 2017;Yan et al, 2018). Limited information is available regarding the effect of FABP4 on milk production traits in livestock.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of FABP4 variation on milk production traits might also be explained by other phenomena. Besides its direct effects on milk production traits, FABP4 has been shown to have an effect on residual feed intake and feed efficiency (Cohen-Zinder et al, 2016), subcutaneous fat depth and fatty acid composition of carcass (Hoashi et al, 2008), intramuscular fat (Lee et al, 2010), marbling score and back-fat thickness (Ardicli et al, 2017), and insulin resistance (Hotamisligil and Bernlohr, 2015). Many investigations have shown associations between milk production traits and these traits.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the approximately 14 million total cattle count, the Holstein breed has a significant impact on Turkish animal husbandry (Turkish Ministry of Food, Agriculture and Livestock Database, 2015). Therefore, evaluating the potential of Holstein meat can be considered as a strategically important point in breeding programmes and meat production (Ardicli et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 show that the frequency of allele A was higher (73%) than that of allele B (27%) . Shin et al (2012) and Ardicli et al (2017) reported that the frequency of allele B was higher (67%) than that of allele A. In this concept, the allele and genotype frequencies are known to vary between breeds and even between the different populations within the same breed (Ardicli et al, 2017).…”
Section: Allelic and Genotypic Frequenciesmentioning
confidence: 99%
“…Also, it was found that FABP4 is a very important candidate gene for the quantitative trait locus and which affects fatty acid deposition and growth performance in pigs (Ojeda et al, 2006) and chicken (Wang et al, 2006). On the other hand, some studies (Shin et al, 2012 andArdicli et al, 2017) did not detect an association between the absence/presence of the alleles in the FABP4 genotype and carcass traits in cattle. The present results support the idea that FABP4 variation may be affect positively the growth and carcass traits in Egyptian Ossimi lambs.…”
Section: Effect Of the Presence/absence Of Fabp4 Alleles In Lambs Genmentioning
confidence: 99%